(3GdefgLjI dHMhK GdYdhe GdGbJUGOjI (B:s (3cJGHI Chd HMK , eQGMd cJGHI GdHMK GdYdej,GdETQGa h GdefGbTI (B/s - (3Hf MehO, ScjfIs ((3GdLRGFQ(B: s (3JOjcdJ(B, s, 2019)
(3GdefgLjI h GdHMK GdYdej , cja JcJH HMKG dChd eQI aj GdYdhe GdGbJUGOjI , efGgL GdHMK GdYdej , eQGMd cJGHI GdHMK GdYdej , GdGTQGa Ydi HMhK GdeGSJQ h GdeGLSJjQ h GdOcJhQGgh CNjQG efGbTI HMhK GdeGSJQ h GdeGLSJjQ h GdOcJhQGg(B.s
(3eQGLY U(B.186s
Keywords: (3GdHMK GdYdejs; (3GdefgLjIs